A configurational analysis of the antecedents of entrepreneurial orientation. Issue 2 (April 2017) - Pittino, Daniel; Visintin, Francesca; Lauto, Giancarlo
Abstract: Entrepreneurial orientation is widely acknowledged as a strong predictor of firm performance. It is therefore critical to understand the factors and conditions that nurture it. In this paper, we investigate what configurations of motivations and personality traits trigger entrepreneurial orientation in three strategic leadership situations: successor of a family business, family-oriented founder, non-family founder. Strategic leaders in these situations are differently exposed to the opportunities and constraints to pursue entrepreneurial posture, because of the influence of family embeddedness and organizational resistance. We apply Fuzzy Set Qualitative Comparative Analysis to a sample of 257 Italian SME owner/managers. We identify 12 coherent configurations of internal and external motivations, and personality traits that are all conducive to entrepreneurial orientation. These configurations are consistent with features of the family and organization environments in which the entrepreneurial action takes place; furthermore, in each strategic leadership situation, different configurations of attributes lead to entrepreneurial orientation.